Mapping James Moffett: Formative Assessment and Common Core Standards for the Contemporary Language Arts Classroom - Jonathan M. Marine; Ruth Nathan (Journal of the Assembly for Expanded Perspectives on Learning, 2024)
In this article, we argue for an expanded conception of language assess-ment based on the principles of James Moffett and centered on outfitting teachers with useful information with which to guide their practice and optimize student learning. Importantly, we begin the article by demonstrating that Moffett’s interest in assessing language growth occurs much earlier than previously thought. Then, we sketch a composite view of Moffett’s evolving views on assessment as drawn from works across the span of his career while also investigating the many thinkers who influenced his ideas in order to situate them in the historical and educational con-text from which they emerged. Next, we present a selection of his growth sequences in order to take up both the principles which undergird them and their potential value for pedagogical practice while also mapping them to Common Core Readi-ness Anchor Standards (CCRAS). Finally, we discuss the implications of Moffett’s work for writing assessment, educational policy, and national assessment standards.
Keywords: JAEPL Moffett